Peran Etika Pendidikan dalam Membentuk Profesionalisme di Fakultas Kedokteran - Siska Anggreni Lubis (Deli Medical and Health Science Journal, 2025)
Educational ethics play a crucial role in shaping students' character, particularly in Medical Schools, where students are expected to apply moral values and professionalism in their medical practice. This paper aims to explain the importance of educational ethics within the context of medical education, and to identify ethical violations commonly occurring among students, faculty, and educational staff. The study employs a qualitative descriptive analysis method, utilizing an internet-based literature review and observation of academic articles related to educational ethics and academic integrity. The findings indicate that ethical violations, such as plagiarism, academic dishonesty, and abuse of power, frequently occur, which can undermine academic integrity and the moral values of the profession. Therefore, it is essential for medical schools to integrate ethics and morality into the curriculum, either through dedicated modules or additional courses addressing medical ethics. This paper is expected to offer solutions to enhance the understanding of educational ethics and prevent future ethical violations.